2011
DOI: 10.1021/la200494r
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Organometallic Polymer Grafts: Electrochemical Switching of Surface Properties and Current Mediation Behavior

Abstract: Quantitative adherence and friction measurements between atomic force microscopy (AFM) tips and reversibly oxidized and reduced poly(ferrocenyl dimethylsilane) (PFDMS) molecular layers grafted to Au are reported. Poly(ferrocenylsilanes) (PFSs) such as PFDMS owe their redox responsiveness to the presence of ferrocene units, bridged by substituted silicon units, in the main chain. Polymers were obtained by anionic polymerization, which allowed us to copolymerize sulfur containing end groups that facilitated graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…12,13 Moreover, the bending transition triggered in the PFS-SO 3 − films may also change the friction between the surface and a counter surface, which would be a topic of great interest to study. 54,55 ■ ASSOCIATED CONTENT * S Supporting Information SEM image of the PS colloid used for pull-off forces in AFM ( Figure S1), XPS spectra and atomic concentration of the different elements in PFS-I and PFS-SO 3 − (Figure S2), cyclic voltammogram of PFS-I in a 0.1 M solution of NBu 4 PF 6 in acetonitrile ( Figure S3) and i−t curve for a PFS-I film ( Figure S4). The Supporting Information is available free of charge on the ACS Publications website at DOI: 10.1021/acs.langmuir.5b01105.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…12,13 Moreover, the bending transition triggered in the PFS-SO 3 − films may also change the friction between the surface and a counter surface, which would be a topic of great interest to study. 54,55 ■ ASSOCIATED CONTENT * S Supporting Information SEM image of the PS colloid used for pull-off forces in AFM ( Figure S1), XPS spectra and atomic concentration of the different elements in PFS-I and PFS-SO 3 − (Figure S2), cyclic voltammogram of PFS-I in a 0.1 M solution of NBu 4 PF 6 in acetonitrile ( Figure S3) and i−t curve for a PFS-I film ( Figure S4). The Supporting Information is available free of charge on the ACS Publications website at DOI: 10.1021/acs.langmuir.5b01105.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…We propose that the large difference between perchlorate anions and the other anionic structures in PFS release kinetics is related to ion pairing (complexation) interaction with ferrocium groups. This can be rationalized based on the ionic radius of ClO À 4 and its high polarizability promoting interactions and ion pairing [43][44][45][46]. Nishiyama et al [43] showed the direct detection of ClO À 4 complexes with the ferrocenium moieties using in situ Fourier transform (FT) Raman spectroelectrochemistry.…”
Section: Bilayers In Fourmentioning
confidence: 99%
“…The adherence and friction of the films were reversibly controlled from an oxidised state (high adhesion, high friction) to a reduced neutral state (low adhesion, low friction), with the gold substrate an electrode. 187 This electrode rectification behaviour could be useful in applications in thin film devices based on PFS films. Gold electrodes have also been modified by cathodic reduction of the Au substrates, immersed in a solution of imidazolium−functionalised PFS chains in the poly(ionic liquid), 1-ethyl-3-methylimidazolium ethyl sulfate.…”
Section: Layer-by-layer Assembly Of Water-soluble Polyferrocenylsilanmentioning
confidence: 94%